PERCEPTIONS OF HEALTH PROFESSIONAL STUDENTS REGARDING WATERPIPE SMOKING AND ITS EFFECTS ON ORAL HEALTH - Shuja, Salman; Hussain, Azmina; Malik, Sofia; Rizwan, Tahir; Amin, Muhammad; Choudhry, Ziaullah (Journal of Ayub Medical College Abbottabad, 2018)
Background: Globally approximately 100 million people are waterpipe smokers and this trend also prevails in Pakistan. It has detrimental effects on general health and oral health. The objective of the study was to determine the perception of health professional students regarding waterpipe smoking (WPS) and to assess their awareness about adverse effects of WPS on oral health. Methods: A self-administered questionnaire based cross-sectional study was conducted among health professional students in three medical and dental institutes of Karachi from December 2015 to February 2016. Results: Study sample comprised 342 students with mean age of 21.36±1.609 years. About 40% of participants ever had shisha and 10% were current smokers; 237 (69.3%) claimed that waterpipe smoking had detrimental effects on oral and general health. A proportion of 33.6% of the total respondents were unaware that waterpipe smoking was the reason for stained teeth, whereas 51.5% did not know that waterpipe smoking was related to dental caries, and 52% and 48% were unaware that waterpipe smoking was the reason for bad taste and halitosis respectively. Approximately 10% of the respondents did not know that waterpipe smoking was a risk factor for the development of oral diseases and oral cancer. Conclusion: There was a scarce knowledge about the hazardous effects of waterpipe smoking on general and especially on oral health. Health professionals need to be aware of hazardous effects of waterpipe smoking so they may play a role in reducing this habit in masses. Keywords: Waterpipe smoking; health professional students; oral health